Authentic Leadership and Its Role in Registered Nurses' Mental Health and Experiences of Workplace Bullying - Nadira Salman Al-Hassan RN, Master student; Ahmad Hussien Rayan PhD; Manal Hassan Baqeas RN, PhD student; Shaher H. Hamaideh PhD, MSc, RN; Huthaifah Khrais PhD, RN (SAGE Publishing, 2023)
Introduction Bullying is a widespread problem in healthcare organizations, resulting in nurses' poor mental health. Effective leadership, such as authentic leadership, may help to overcome this problem. Objective To examine the relationship between authentic leadership, workplace bullying, and nurses' mental health, controlling for demographic characteristics. Methods A descriptive correlational design was utilized with a sample of 170 nurses. Nurses were recruited from four private hospitals in Jordan and completed a survey about their perception of managers' authentic leadership, their experience of workplace bullying, and their mental health. Results About 48.8%, 25.9%, and 25.3% were categorized as "not bullied," "occasionally bullied," and "severely bullied," respectively. Participant nurses had mild depression ( m  = 12.11) and moderate anxiety ( m  = 10.92). Workplace bullying was higher among nurses who earn less than 600 Jordanian dinars and nurses working in the smallest hospital, with 130 beds. Authentic leadership explains 6% of the variance of workplace bullying, 3% of anxiety, 7% of stress, and 7% of depression above and beyond the variance explained by other variables. Conclusions Healthcare organizations are facing a challenge in providing a healthy work environment. Employing authentic leadership in the workplace could be one of the factors that could help in addressing this issue.